ETIKA DAN TANGGUNG JAWAB SAINS DALAM PERSPEKTIF ISLAM - Kerwanto, Kerwanto (Universitas Muhammadiyah Tangerang, 2024)
Rapid technological developments often ignore aspects of humanity and morality. As if science is separate from Islamic teachings. This paper examines the relationship between ethics, scientific responsibility, and Islamic teachings in the context of contemporary scientific and technological developments. Through a comprehensive analysis method, this literature study explores how Islamic ethical principles can be integrated with modern scientific ethical standards to form a strong framework for guiding technological research and development. The results of the analysis show that the integration of Islamic values with modern scientific ethics can create a scientific paradigm that is not only innovative, but also ethical, responsible, and beneficial to all humanity. This study concludes that a holistic approach that combines spiritual, moral, and practical considerations can bridge the gap between technological progress and human values, and encourage the development of science that is in line with ethical principles and social justice.